Can we improve the conditioning regimen before autologous stem cell transplantation in multiple myeloma?. (2nd November 2017) - Martino, Massimo; Recchia, Anna Grazia; Console, Giuseppe; Gentile, Massimo; Cimminiello, Michele; Gallo, Giuseppe Alberto; Ferreri, Anna; Naso, Virginia; Irrera, Giuseppe; Messina, Giuseppe; Moscato, Tiziana; Vigna, Ernesto; et al.
ABSTRACT: Introduction : High-Dose Chemotherapy and Autologous Stem Cell Transplantation (ASCT) has long been established as the standard of care for eligible patients with newly diagnosed multiple myeloma. Although many studies have been performed in the induction, consolidation and maintenance settings, few trials have been dedicated to conditioning regimens before ASCT. Areas covered : We reviewed all the reported experiences and illustrate current knowledge in the field of conditioning regimens. Expert opinion : High-Dose Melphalan (MEL) at the dosage of 200 mg/m 2 is the standard conditioning regimen. However, a variety of strategies have been explored, including MEL dose escalation which involves the addition of other agents such as busulfan, thiotepa, bendamustine, proteasome inhibitors, and immunomodulatory drugs or monoclonal antibodies. Overall, such strategies have mixed results. The lack of randomized trials using these agents and the fact that they include different study populations makes it difficult to compare across studies. Prospective, randomized trials are needed to test novel conditioning regimens containing double alkylating agents or novel agents, including new MEL formulations. Only large phase III studies specifically aimed at investigating the safety, therapeutic activity, and cost/efficacy relationships can provide the answer in the continuous debate surrounding new conditioning regimens for ASCT.